«Con li suoi vestimenti asciugare il morto viso della salata acqua, e bagnarlo di molte lagrime»: la «Fiammetta» en el «Leànder y Hero» de Roís de Corella - Martos, Josep Lluís (Caplletra. Revista Internacional de Filologia, 2005)
The «Elegia di madonna Fiammetta» has an evident impact of the story of Leandre and Hero, especially in the moments in which the lady suffers while waiting for her lover, who never comes. Fiammetta makes obvious this parallelism on severaloccasions, and manages to invent an end for the story loaded of pathos. Joan Roís de Corella realises about this relationship between both two works and makes the inverse path: he uses the tone and some narrative elements of the Elegia for writing his Leander and Hero. It is demonstrated that the so contreversial end of Corella’s story is not original of the Valencian, but it also depends on Boccaccio’s text.